Hydraulic conductivity and calcium carbonate content of biocemented heavy-metal contaminated mine waste soil - Makinda Jodin; Kassim Khairul Anuar; Ahmad Kamarudin; Muhammed Abubakar Sadiq; Zango Muttaqa Uba (E3S Web of Conferences, 2021)
It is not uncommon for mining activity to generate wastes associated with negative engineering impacts include susceptibility to runoff due to the absence of vegetation, erosion, and sinkhole. Due to their high degree of permeability, movement of heavy metal contaminants in waste soils and aquifers occurs actively along with the hydrogeological parameters, and research on using biocementation methods such as enzyme induced calcite precipitation (EICP) to reduce the hydraulic conductivity is therefore beneficial. Mine waste soil collected from a copper mine in Lohan Dam, Sabah is characterized physically, morphologically, and chemically then treated with EICP under different operational parameters include curing duration (1,3,7 days), curing temperatures (5, 10, and 25 oC ), and relative density (70 and 80 %). The hydraulic conductivity was then tested using a constant head permeability test and the calcium carbonate content (%) is determined using the HCL washing method. Properties of the Lohan Dam wastes are found to be predominantly coarse grain soil of low plasticity, high specific gravity, high permeability, acidic in nature, and low organic content. Morphologically, they are composed of powdered and hardened particles with dark brown color with high amount of irregular-shaped particles. Mineralogical, Lohan Dam soil wastes contain a high level of heavy metals beyond the safety level of the Department of Environmental Malaysia. EICP treatment had to change the degree of permeability from ‘high and medium’ to ‘low’ with a 94-97% reduction in hydraulic conductivity corresponding to the amount of calcium carbonate content produced ranging 6.94-9.63%. In conclusion, relative density shows the marginal effect, curing duration, and temperature shows a more significant impact on the treatment effectiveness.